The Attitudes Toward and Perceived Communicative Competence of Individuals with Aphasia using Speech Generating Devices - Brock, Kristofer L. (2021)
Purpose: The purpose of this dissertation was twofold. Study one established the reliability and validity of the Communicative Competence scale (CC scale). Study two investigated the effects of augmentative and alternative communication (AAC) message organization strategies (i.e., taxonomic grids and visual scenes) and respondent group on the attitudes toward and perceived communicative competence of individuals with aphasia. Method: In study one, graduate speech-language pathology (SLP) students viewed two digital recordings of an individual with aphasia interacting with a communication partner using either a taxonomic grid display or visual scene display strategy. The respondents were requested to complete the CC scale and the Conversational Skills Rating Scale (CSRS; Spitzberg & Adams, 2007). In study two, the same two digital recordings were viewed by 113 respondents (i.e., healthcare professional students, non-health science students, and caregivers of individuals with aphasia). The respondents were requested to complete the Attitudes Toward Nonspeaking Persons scale (ATNP; Gorenflo & Gorenflo, 1991) and the CC scale. Data for both studies were analyzed using a multivariate analysis of variance (MANOVA). Results: Results of study one indicated that the CC scale is a reliable and valid measure of perceived communicative competence for individuals with aphasia who use speech-generating devices. Two reliable constructs underlined the CC scale. Results of study two indicated significant (p < .05) main effects for message organization strategy and respondent group. Visual scene displays had a significantly (p < .05) more favorable impact on communicative competence ratings than taxonomic grid displays. Further, caregiver ratings were significantly (p < .05) more favorable than ratings provided by other groups. However, no significant effects were observed for the attitude variable. Conclusion: Visual scenes appear to positively influence the perceived communicative competence of individuals with ...